Histological assessment of thermal damage in porcine muscle induced by monopolar electrosurgical cutting devices during manual and robotic testing - Elzbieta Ewertowska; Vincent J. Casey; Robert Whiting; Micheal Burke; Laura Frey; Paul Sheridan; Ben Row; Bryan Deeny; Laoise M. McNamara (International Journal of Hyperthermia)
Surgical cutting with electrosurgical tools facilitates tissue dissection and vessel sealing, preventing blood loss. The extent of tissue necrosis due to temperature elevations is dependent on the cutting technique, device design, coating properties and power settings, but the influence of these parameters is not fully understood. Here we conduct a comprehensive comparative analysis of thermal damage comparing (1) manual user-controlled and robotic electrosurgical cutting approaches for (2) varying electrodes and coatings, and power settings. We demonstrate that ceramic coating significantly enhanced cutting performance and cut quality and reduced lateral thermal damage, by 86.15% at 35 W and 65% at 50 W respectively. We provide quantitative assessment of the influence of surgical variability on thermal damage, comparing robotic and manual electrosurgical cutting. Robotic cutting with one ceramic electrosurgical coated device reduced thermal damage (midline − 47.42%, lateral − 33.06%), whereas for the other coated electrode the thermal spread increased (midline − 66.57%, lateral −245.72). Thus, thermal damage performance was strongly influenced by surgical variability and the specific characteristics of each device. Together, these results provide an enhanced understanding of potential mechanisms determining electrosurgical outcomes. Understanding of these interdependencies and mechanisms of action linked to a specific electrosurgical system is essential for successful tissue resection.